Subduction modulated the long-term oxygenation of Earth’s surface - Wei Shi; Chao Li; Benjamin J. W. Mills; Michael Brown; Tim E. Johnson; Thomas J. Algeo; Mingcai Hou; Chunlian Wang; Mingyu Zhao; Simon W. Poulton (Proceedings of the National Academy of Sciences, 2026)
On Earth, atmospheric oxygen is inferred to have risen over three major intervals before reaching modern levels, with each interval having a profound impact on the evolution of the biosphere. However, the principal driver behind these stepwise increases remains elusive. Here, we compile metamorphic thermobaric ratios ( T / P ) through time and use them as a first-order, probabilistic proxy for the likelihood of “cold” subduction (i.e., with T / P < 375 °C GPa –1 ) during secular cooling of Earth’s mantle. Then, we couple this tectonic forcing to biogeochemical modeling to test whether more efficient cold subduction may have enhanced the net transfer of reduced organic carbon and pyrite to Earth’s deep interior, thereby diminishing oxygen sinks and allowing surface oxygen levels to increase at geological timescales. Modeling results indicate that the progressive emergence of cold subduction could plausibly have contributed to the long-term oxygenation trajectory and associated secular trends in atmospheric carbon dioxide, seawater sulfate, sedimentary phosphorus, and marine redox conditions. Although the absolute magnitudes remain uncertain, the predicted trajectory of surface oxygenation is qualitatively consistent with the broad three-step pattern inferred from geochemical proxies. We propose that the progressive evolution of subduction may have been a key driver of long-term surface oxygenation, linking mantle cooling to the rise of conditions favorable for aerobic lifeforms.